Representation of Human and Environmental Relations in the Novel“Mausim al-Hijrah ila al-Syimal ” by Tayyib Salih: An Ecocritical Studyby Greg Garrard - Syauqi, Mohammad Syauqi Abdullah; Muassomah (Universitas Negeri Semarang, 2025)
Ecocritical studies in literature have increasingly developed alongside growing awareness of the relationship between humans and the environment. The novel Mausim al-Hijrah ila al-Syimal by Tayyib Salih, set in Sudan, presents a narrative about human interaction with nature in a postcolonial context. This study aims to analyze the representation of human-environment relationships in the novel using Greg Garrard’s ecocritical approach. The focus of this study includes six key concepts of Greg Garrard’s ecocriticism: pastoral, pollution, wilderness, apocalypse, dwelling, and animals. This research employs a qualitative descriptive method with an ecocritical approach. Data collection techniques include reading, marking, and noting relevant texts. Data analysis follows Miles and Huberman’s framework: data reduction, data display, and conclusion drawing. The findings reveal two main types of human-environment relationships in the novel. The conflictual relationship is reflected in (1) pollution, symbolizing modernization and its detrimental effects on the environment; (2) wilderness, portraying human struggles and powerlessness against nature’s forces; and (3) apocalypse, depicted through natural disasters like catastrophic floods that disrupt society. Meanwhile, the harmonious relationship is illustrated in (1) pastoral, representing nostalgia for rural life and criticism of modernization; (2) dwelling, highlighting the emotional attachment between humans and their living spaces; and (3) animals, showing their role in daily life as part of the social and ecological system. These findings indicate that Mausim al-Hijrah ila al-Syimal not only critiques environmental exploitation and modernization’s impact but also emphasizes human attachment to nature. This study is expected to expand the understanding of ecocriticism in postcolonial literature and uncover the complexity of human-environment interactions.